Duplex real-time polymerase chain reaction assay for the detection of human KIPyV and WUPyV in nasopharyngeal aspirate pediatric samples. (August 2018) - Ligozzi, Marco; Galia, Liliana; Carelli, Maria; Piccaluga, Pier Paolo; Diani, Erica; Gibellini, Davide
Abstract: In this study, we describe a duplex real-time PCR assay for the simultaneous detection of KIPyV and WUPyV polyomaviruses based on TaqMan probes. This assay detected 500 copies/mL both for KIPyV and WUPyV in 100% of tested positive samples. We assessed this technique on 482 nasopharyngeal aspirate specimens from hospitalized pediatric patients with respiratory symptoms, previously analyzed with commercial multiplex assay for 16 major respiratory viruses. Our assay detected KIPyV genome in 15 out of 482 samples (3.1%) and WUPyV genome in 24 out of 482 samples (4.9%), respectively, and in three samples the coinfection of the two viruses was found. Interestingly, 29 out of 36 of samples with KIPyV and/or WUPyV infection exhibited a co-infection with one or more respiratory viruses confirming that KIPyV and WUPyV were often detected in association to other viral infections. Of note, KIPyV and WUPyV were detected singularly in 4 out of 15 cases and 3 out of 24 cases, respectively, suggesting a possible direct role of these viruses in the respiratory diseases. In conclusion, this method could be taken into account as an alternative technical approach to detect KIPyV and/or WUPyV in respiratory samples for epidemiological and diagnostic analyses. Highlights: Duplex real-time PCR assay for the detection of human KIPyV and WUPyV was assessed. This assay was evaluated on nasopharyngeal aspirate samples from pediatric patients. KIPyV and WUPyV were detected in 3.1% and 4.9% of samples, respectively.